Polymorphism evidence in Plasmodium (Haemamoeba) lutzi Lucena, 1939 (Apicomplexa, Haemosporida) isolated from Brazilian wild birds. (June 2019) - de Oliveira, Luísa; Cedrola, Franciane; Senra, Marcus Vinicius Xavier; Scopel, Kézia Katiani Gorza; Martinele, Isabel; Tostes, Raquel; Dias, Roberto Júnio Pedroso; D'Agosto, Marta
Abstract: Plasmodium parasites can infect great variety of bird species around the world inflicting the so called avian malaria, an illness that could be fatal in some cases and consequently, should be monitored and widely included into conservation programs. The aim of this study was to characterize two lineages of Plasmodium (Haemamoeba) lutzi found in some birds in the Atlantic Forest of Minas Gerais - Brazil, that were morphologically identified after blood smears analyses under light microscopy and molecularly by sequencing the mitochondrial cytochrome b gene ( cyt b ). Besides these two lineages could be clearly morphologically identified as P.(H.) lutzi, some variations in comparison with its original description were noticed: absence of meronts and gametocytes (early and fully grown) in polychromatic erythrocytes, the larger size of pigment granules in meronts and gametocytes, and the presence of small vacuoles between pigment accumulation in fully grow macrogametocytes. Moreover, a certain degree of genetic intraspecific diversity was also observed across the lineages of P. (H.) lutzi, indicating the existence of polymorphisms within this taxon, which is uncommon in Haemosporida. These results allow discussion about species boundaries within avian hemosporidians and highlight the importance of multidisciplinary approaches for a more efficient species identification and characterization. Graphical abstract: Unlabelled Image Highlights: First survey on polymorphism and intraspecific genetic variability of haemosporidian parasites in brazilian birds. Detailed morphological of Plasmodium ( Haemamoeba ) lutzi and phylogenetic relationships of this species. Important approaches to species delimitation within Haemosporida.